Polymer photovoltaics a practical approach - Krebs, Frederik C. (SPIE Press, 2008)
This book is intended to be a practical guide in the laboratory for the experimental solar-cell scientist whether he or she is involved with synthesis, device preparation, processing, or device characterization. Useful to all scientists working practically in the field, the book presents the process of creating a polymer solar-cell device beginning with a description of materials, including how they are made and characterized, followed by how the materials are processed into devices and films, and how these are characterized. From there, the status of two emerging fields of polymer solar cells are described: degradation and stability and large-scale processing.
"PM175"--P. [4] of cover.
Keywords: Photovoltaic cells -- Materials.; Conducting polymers.; elektronické knihy; electronic books